Visualisation of influenza A protein segments in distance invariant self-organising map. (1st January 2012) - Cheng, Wei-Chen; Liou, Cheng-Yuan
Due to the lateral gene transfer, the phylogenetic tree could be inadequate for representing the evolution of virus. This paper employs the distance invariant manifold (Cheng and Liou, 2009) to display the collection of influenza A in a cubic space. This space provides a global view of the evolution of the whole family vividly.